Effect of Bap (Benzyl amino purine) Concentrations on Shoot Multiplication of Two Varieties of Kepok Banana In Vitro - Ilmiyah, Isnanda Rosyidatul; Maftuchah; Muhidin (Universitas Muhammadiyah Malang, 2022)
Banana production in Indonesia has decreased due to the lack of availability of healthy seeds. The purpose of this study was to determine the effect of BAP on the multiplication of two banana varieties (Kepok Manurun and Kepok Unti Sayang) by in vitroculture. This study used a completely randomized design (CDR) in a factorial manner with 2 factors. The first factor was the banana variety (Kepok Manurun and Kepok Unti Sayang), the second factor was the concentration of BAP ZPT (0, 1, 2, 3) with 4 replications where each replication consisted of 4 samples, each bottle was planted with 1 plantlet for a total of 128 bottles. The results showed that the concentration of BAP did not affect the multiplication of two kepok banana varieties in vitro. The BAP concentration of 2 ml/l produced the highest number of shoots of 1,91 shoots, the concentration of BAP of 1 ml/l produced the highest number of leaves of 1,52 leaf, while the concentration of BAP 0 ml/l or without BAP result in the highest plant height of 1,05 cm. While the highest number of roots was found in the BAP treatment of 1 ml/l, the number of root tips, the highest root length was found in the BAP treatment 0 ml/l, while the concentration of BAP 2 ml/l produced the highest number of tillers of 1,39 tillers, and the concentration BAP 1 ml/l resulted in a stem diameter of 3,98 cm